Copper oxide nanoparticles for photocatalytic and antibacterial applications: a review - Le Minh Huong; Le Tan Tai; Nguyen Hung Vu; Nguyen Thanh Hoai Nam; Nguyen Minh Dat; Hữu Hiếu, Nguyễn (Vietnam Journal of Science and Technology, 2025)
Copper oxide (CuO) is a well-known semiconductor material, which has been widely used in many different fields such as energy, environment, and medicine. The need for effective and feasible synthesis of a nanostructured CuO for various applications is an urge. Therefore, the method for synthesizing CuO with different approaches is summarized in this review to shed light on the viable options for synthesizing this promising material. In addition, applications of CuO in various fields is discussed, in turn, the main application of CuO in the photodegradation of organic pollutants and antibacterial properties is presented in detail. Future perspectives are also given to mention and tackle the current and future challenges for the synthesis as well as the application of the material.